(untitled) (JED (Jurnal Etika Demokrasi), 2022)
This study aims to determine the social adaptation of new students of Master of Sociology Education FKIP Untan related to the application of the blended learning system in the era of the covid 19 pandemic. The research method used was a survey method through a questionnaire assisted by Google Forms and an online interview guide conducted to the entire (population) 8 students. newpostgraduate program as a research informant. Data collection techniques were carried out by direct and indirect communication techniques. Data collection tools in the form of questionnaires and online interview guides. The results showed that the new master students of sociology education at FKIP Untan, were already ready and able to adapt socially in the good category because they mastered IT (87.5%) in the implementation of the blended learning system and in the very good category because they mastered IT and lecture materials (12.5%). %) in the era of the covid 19 pandemic. There are eight empirical obstacles in the field when implementing blended learning / social adaptation problems: from the results of online interview answers and answers to questionnaires via google form in the form of (1) unstable internet wireless network connection disturbance, (2 ) electricity network (local) that often goes out, (3) limited equipment (4) understanding/skills in using ICT, (5) delays in work, and/or sending assignments for lecture materials to lecturers, quizzes and deepening of material, (6 ) busy activities outside of lectures, (7) limited time involved in online lectures and (8) internet quota/package. Penelitian ini bertujuan untuk mengetahui adaptasi sosial mahasiswa baru magister pendidikan sosiologi FKIP Untan berkaitan dengan penerapan system blended learning di era pandemi covid 19. Metode penelitian yang digunakan adalah metode survey melalui kusioner berbantuan google form dan panduan wawancara daring dilakukan kepada seluruh ( populasi) 8 mahasiswa baru program pascasarjana selaku informan penelitian. Teknik pengumpulan data dilakukan dengan teknik komunikasi langsung dan tidak langsung. Alat pengumpulan data berupa angket dan panduan wawancara daring. Hasil penelitian menunjukkan bahwa mahasiswa baru magister pendidikan sosiologi FKIP Untan, ternyata telah siap dan mampu beradaptasi sosial terkatagori baik karena menguasai IT (87,5%) dalam pelaksanaan system blended learning dan terkatagori sangat baik karena sangat menguasai IT dan materi kuliah (12,5%) di era pandemi covid 19. Ada delapan kendala secara empiris di lapangan saat pelaksanaan pembelajaran blended /masalah beradaptasi sosial: dari hasil jawaban wawancara daring dan jawaban angket via google form berupa (1)gangguan koneksi jaringan nirkabel internet yang tidak stabil, (2)jaringan aliran listrik (lokal) yang sering padam,(3)keterbatasan perangkat (4)pemahaman /ketrampilan penggunaan ICT, (5) keterlambatan pengerjaan, dan/atau mengirim tugas-tugas materi kuliah kepada dosen, kuis serta pendalaman materi,(6)kesibukan kegiatan diluar perkuliahan, (7)keterbatasan waktu keterlibatan dalam perkuliahan daring dan (8) kuota / paket internet yang dimiliki.